The usability analysis for the use of augmented reality and visual instructions in navigation services - Basiri, Anahid; Amirian, Pouria; Winstanley, Adam (2016)
The use of Augmented Reality and visual cues as a part of navigational instructions, in addition to conventional audio and textual instructions, may improve the experience of the users of the navigation services. This approach can be also more compatible with the way people give instructions in everyday life; People usually associate directions with visual cues (e.g. “turn right at the square”) when giving navigational instructions in their daily conversations. In this regard, landmarks as the unique and easy-to-recognise features can play an important role. Such easy to remember features, which are available both indoors and outdoors, can be helpful when exploring an unfamiliar environment. A Landmark-based navigation service can make users sure that they are on the correct route, as the user is reassured by seeing the landmark whose information/picture has just been provided as a part of navigational instruction. Such advantages of use of landmarks visual information as a part of the instructions can decrease the time of travel and improve the experiences of the users. This paper assesses how landmarks can improve the performance of pedestrian movements following landmark-based navigational instructions.